Collaborative Governance in Addressing Open Unemployment Rates at the DKI Jakarta Provincial Manpower, Transmigration and Energy Office - Olifvia Dwiyanti; Rosyidatuzzahro Anisykurlillah (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
The province of DKI Jakarta faces the challenge of a high open unemployment rate, which is among the six highest nationally. This study aims to describe and analyze the implementation of collaborative governance in addressing this issue by the DKI Jakarta Provincial Manpower, Transmigration, and Energy Office in collaboration with the Indonesian Employers Association (Apindo) and the Chamber of Commerce and Industry of DKI Jakarta. Using a descriptive qualitative method with data collection techniques of observation, interviews, and documentation, this study is analyzed through the collaborative process framework by Ansell and Gash. The results indicate that this tripartite collaboration has been effective, characterized by: (1) productive face-to-face dialogue through regular forums and hybrid communication; (2) strong trust-building among stakeholders; (3) high commitment to the process, evidenced by resource allocation; (4) a shared understanding of the root cause of skill mismatch; and (5) significant intermediate outcomes, including a downward trend in unemployment, increased labor absorption, and the realization of programs such as industry-based training and Job Loss Insurance. These findings confirm that the collaborative governance approach is an effective strategy for tackling open unemployment in metropolitan areas